1995
DOI: 10.3109/07420529509064504
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Dopamine and Cholecystokinin in Nucleus Accumbens and Striatum of Rats—Influence on Dopaminergic Stimulation

Abstract: The concentrations of cholecystokinin (CCK) and dopamine (DA) were determined in the nucleus accumbens (anterior, posterior) and striatum of rats every 2 h during a period of 24 h. For both substances, a circadian rhythm was found, which was best fitted by a dominant 24-h period superimposed by the second (12 h) and fourth (6 h) harmonics. The rhythms in CCK and DA were negatively correlated because of a difference in phase position by approximately 3 h. A dominant DA peak was found in the light phase coincidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…It is likely that CLOCK also contributes to the strong circadian rhythm in Cck expression. 34, 35 As expected by the sequence of the CLOCK∆19 protein, this protein can still bind to the Cck promoter but cannot activate transcription. We find that levels of H3K4me3, a histone modification associated with transcriptional activation, are decreased at the Cck promoter when compared to WT mice.…”
Section: Discussionmentioning
confidence: 87%
“…It is likely that CLOCK also contributes to the strong circadian rhythm in Cck expression. 34, 35 As expected by the sequence of the CLOCK∆19 protein, this protein can still bind to the Cck promoter but cannot activate transcription. We find that levels of H3K4me3, a histone modification associated with transcriptional activation, are decreased at the Cck promoter when compared to WT mice.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that plasma dopamine and its metabolites changes with circadian rhythm not only just in humans (Sowers and Vlachakis, 1984), but also in CSF in primate animals (Perlow et al, 1977) and in the striatum of rat (Schade et al, 1995; Castaneda et al, 2004). Another study indicated that the dopamine receptor responsiveness is modulated by the circadian rhythm at the level of spinal cord in decapitated Drosophila melanogaster (Andretic and Hirsh, 2000).…”
Section: Clinical Presentations and Diagnostic Criteriamentioning
confidence: 99%
“…Our laboratory and others have reported time-of-day differences in DAT and TH protein levels (Sleipness et al, 2007b, Webb et al, 2009a, Webb et al, 2009b) and in DAT function (Sleipness et al, 2008) in the mPFC and nucleus accumbens. Several other groups have also demonstrated diurnal or circadian changes in dopamine and its metabolites (O’Neill and Fillenz, 1985, Paulson and Robinson, 1994, Schade et al, 1995, Paulson and Robinson, 1996, Feenstra et al, 2000, Castaneda et al, 2004, Webb et al, 2009a) and in dopamine D2 receptor function (Tonissaar et al, 2006). However, as far as we know, the influence of altered photoperiod on DAT and TH within the mesocortical/mesolimbic DA system has not been examined.…”
Section: Discussionmentioning
confidence: 99%